108k views
2 votes
Solve for x.
5(x - 3) + 4(x + 3) = 3(x - 1)
What’s the answer ?

2 Answers

4 votes

Answer:

5x -15 + 4x + 12 = 3x -3

5x + 4x - 3x = 15 - 12 - 3 (put all like terms in one side)

6x = 0

x = 0/6

x= 0

User Mook
by
4.7k points
4 votes

Answer:

x=0

Explanation:

Solve for x.

5(x - 3) + 4(x + 3) = 3(x - 1)

Distribute

5x -15 +4x +12 = 3x-3

Combine like terms

9x -3 = 3x-3

Add 3 on each side

9x -3+3 = 3x-3

9x = 3x

Subtract 3x from each side

9x-3x = 3x-3x

6x =0

Divide by 6

6x/6 = 0/6

x=0

User Ed Avis
by
4.4k points